Preparation of Straw Biochar by Solid Phase Activation and Its Deodorization Performance Ｒesearch - LI You-jing; LI Fen; YANG Ying; GE Bao-cai; MENG Fan-zhu (Journal of Harbin University of Science and Technology)
To solve the waste of biomass resources and the accumulation of by-product charcoal in the process of biomass pyrolysis. Ｒice straw was used as raw material to prepare straw activated carbon by solid-phase activation，and the structure of activated carbon and the adsorption performance of H2S were compared and analyzed. The results showed that when sodium hydroxide was used as an activator，when the carbonization temperature was 450℃，the activation temperature was 700℃，the material ratio was 1∶2，and the activation time was 60 min，the adsorption time of H2S on the prepared straw activated carbon could reach 86 min. In order to enhance the adsorption performance of activated carbon，urea was selected to conduct secondary activation of straw activated carbon by hydrothermal method. The results showed that the adsorption effect was best when the activation temperature was 120℃，and the material ratio was 1∶ 1 ( mass ratio) ，and the adsorption of H2S could reach 130 min. The analysis shows that the straw activated carbon reactivated by urea has a complex pore structure and the effect of doping nitrogen-containing functional groups，and these factors are conducive to the adsorption of H2S.